Factors Affecting Money Demand in Sudan: Statistical and Analytical Study (1990-2019) - Ahmed, Adel Ali (IJRDO - Journal of Social Science and Humanities Research, 2020)
The study aimed to know the most important factors affecting the demand for money in Sudan, and the study relied on secondary sources where data were obtained from the Bank of Sudan and the Central Statistical Organization, and statistical packages were used in the processing and analysis of data. The result shows the possibility of using the key components in the analysis method. - KMO test was used to measure the adequacy of the sample size and the result shows the lowest correlation was (0.780). Kaiser standard detected three factors with roots value higher than 1.0, these three factors explain 92.422% of the total variation, the first factor contribute to 60.115%, second factor  contribute by 19.115% of the total variance, while the third factor contribute by 13.192% of the total variance. To explain these three factors the study used Varimax method of how the biggest disparity, where the result showed that factors had strong weights, and through the interpretation of factors most of the changes in the money demand during the study period attributable to the change in the monetary and economic indicators. - The study found that the first factor saturated with the following variables (Exchange Rate, GDP (Current prices), Money supply, Public budget, and the currency of the public, Funding, Index Number, Import, and Export). The second factor saturated with the following variables (Inflation, GDP (Fixed prices), and Funding Cost). The third factor saturated with the following variable (Velocity Circulation of Money). The most recommendations of this paper are, the necessity of existence of a sophisticated statistical system to reflect the actual status to planners and policy makers of monetary and economic sectors and Unification of data collection methods according to statistical methods and classification, which will facilitate researcher contributing in the research.